IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PAI BAGI ANAK INDONESIA DI LUAR NEGERI: STUDI KASUS PADA KKN INTERNASIONAL DI MADINAH - Ahmad Yusuf Khoir; Munawir Pasaribu (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Indonesian diaspora children, particularly those residing in Madinah, Saudi Arabia, face complex educational challenges, including cultural dominance and limited access to formal standard Indonesian education. This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) for Indonesian children abroad through the International Kuliah Kerja Nyata (KKN) program. Utilizing a qualitative descriptive case study approach, data were collected through participant observation, semi-structured interviews, and documentation. The findings reveal that university students effectively acted as agents of educational change by adapting the Merdeka Curriculum flexibly and differentiating instruction to foster the Pancasila Student Profile among diaspora children. Personal approaches and learning media innovations were the primary supporting factors, whereas limited infrastructure and local volunteer teachers' lack of understanding of the curriculum served as the main inhibiting factors. The sustainability of this educational innovation heavily relies on systematic synergy between universities and the government.